Perspectives for systems biology in the management of tuberculosis. (26th May 2021) - Kontsevaya, Irina; Lange, Christoph; Comella-del-Barrio, Patricia; Coarfa, Cristian; DiNardo, Andrew R.; Gillespie, Stephen H.; Hauptmann, Matthias; Leschczyk, Christoph; Mandalakas, Anna M.; Martinecz, Antal; Merker, Matthias; Niemann, Stefan; et al.
Standardised management of tuberculosis may soon be replaced by individualised, precision medicine-guided therapies informed with knowledge provided by the field of systems biology. Systems biology is a rapidly expanding field of computational and mathematical analysis and modelling of complex biological systems that can provide insights into mechanisms underlying tuberculosis, identify novel biomarkers, and help to optimise prevention, diagnosis and treatment of disease. These advances are critically important in the context of the evolving epidemic of drug-resistant tuberculosis. Here, we review the available evidence on the role of systems biology approaches – human and mycobacterial genomics and transcriptomics, proteomics, lipidomics/metabolomics, immunophenotyping, systems pharmacology and gut microbiomes – in the management of tuberculosis including prediction of risk for disease progression, severity of mycobacterial virulence and drug resistance, adverse events, comorbidities, response to therapy and treatment outcomes. Application of the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) approach demonstrated that at present most of the studies provide "very low" certainty of evidence for answering clinically relevant questions. Further studies in large prospective cohorts of patients, including randomised clinical trials, are necessary to assess the applicability of the findings in tuberculosis prevention and more efficient clinical management of patients. We are at the doorstep of a new era in which systems biology approaches will contribute to the management of patients with tuberculosis including prediction of risk for disease progression and severity, response to therapy and treatment outcome. https://bit.ly/36DQegb